Inflation Targeting versus Monetary Targeting - Helmut Wagner (Kredit und Kapital, 1999)
Inflation Targeting versus Monetary Targeting Die Diskussion über Inflation Targeting zählt derzeit zu den zentralen Debatten in der Theorie der Geldpolitik. Sie erregte insbesondere öffentliche Aufmerksamkeit bei der Debatte um die geldpolitische Strategie der neugegründeten Europäischen Zentralbank. Inflation Targeting wird von seinen bekanntesten Befürwortern als die effizienteste oder gar die einzig effiziente geldpolitische Strategie angesehen. Diese These wird hier näher analysiert, wobei Inflation Targeting der Konkurrenzstrategie des Monetary Targeting gegenübergestellt wird. Zwei Aspekte werden näher betrachtet: die Effizienz der Zwischenzielwahl zum einen und Transparenz, Verantwortlichkeit und mithin Glaubwürdigkeit der jeweiligen geldpolitischen Strategie andererseits. (JEL E5) – – Inflation targeting is currently one of the key issues in the discussion about monetary policy theory. It attracted public attention especially in the debate about the newly established European Central Bank's monetary policy strategy. The most widely known advocates of inflation targeting like to refer to it as one of the most efficient or even the only monetary policy strategy that is efficient at all. This hypothesis has been closely analysed in this contribution comparing inflation targeting to the competing strategy of monetary targeting. Two aspects have been more closely analysed: The efficiency of the choice of interim objectives on the one hand and transparency, accountability and, thus, credibility of the respective monetary policy strategy on the other.
Keywords: E5; 330